Technological potential of Eucalyptus dunnii wood from different fertilization and genetic sources for the production of edge glued panels - Annah Carolina Bajaluk Bilik; Rosilani Trianoski; Setsuo Iwakiri; Alessandro Camargo Angelo (Maderas: Ciencia y Tecnología, 2025)
Several methods are implemented to improve the quality and productivity of Eucalyptus plantations, including genetic improvement and seedling fertilization. These practices, combined with the favorable soil and climate conditions across much of Brazil, have enabled high yield forest production. These plantations supply raw materials for a wide range of industrial uses, notably the manufacture of wood panels. Among them, edge glued panel are produced by joining battens laterally or on their surface using adhesive bonds. This work aimed to evaluate the technological potential of Eucalyptus dunnii (white gum) wood from different fertilization treatments and genetic sources for the production of edge glued panels. The material was collected from a plantation with trees 8,5 years old in Pinhais, Parana, and included 24 trees: 12 from clonal material and 12 from selected seeds. Each genetic source was subjected to two fertilization treatments (conventional and slow-release) and one control, resulting in six treatments. The wood was analyzed for volumetric, chemical and physical properties. After drying, battens were glued and the strength of the adhesive joints was tested. Clonal trees exhibited the highest volume and the lowest basic density. The lowest anisotropic coefficient was found in wood subjected to slow release fertilization. Fertilization also influenced all aspects of chemical composition. Overall, the treatments with clonal trees and slow release fertilization showed the highest suitability for edge glued panel production, justifying the investment in silvicultural practices from the point of view of wood technology.